Detecting RNA–Protein Interactions With EGFP‐Cy3 FRET by Acceptor Photobleaching. Issue 2 (23rd February 2023) - Alam, Shagufta Rehman; Mahadevan, Mani S.; Periasamy, Ammasi
Abstract: Förster Resonance Energy Transfer (FRET) is a great tool for cell biologists to investigate molecular interactions in live specimens. FRET is a distance‐dependent phenomenon which can detect molecular interactions at distances between 1‐10 nm. Several FRET approaches are reported in the literature for live and fixed cells to study protein‐protein interactions; this protocol provides details of acceptor photobleaching as a FRET method to study RNA‐Protein interactions. Cy3‐labeled RNA foci (FRET acceptors) are photobleached at the intra‐cellular site of interest (the nuclei) and the intensity of the EGFP‐tagged proteins (FRET donors) at that same site are measured pre‐ and post‐ photobleaching. In principle, FRET is detected if the intensity of EGFP increases after photobleaching of Cy3. This protocol describes necessary steps and appropriate controls to conduct FRET measurements by the acceptor photobleaching method. Successful applications of this protocol will provide data to support the conclusion that EGFP‐labeled proteins directly interact with Cy3‐labeled RNA at the site of photobleaching. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol : FRET in fixed cells Alternate Protocol : FRET in live cells